The Impact of Social Media on People's Social Life The perspective of the Qur'an - Devi Rizki Apriliani (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the impact of social media on the social life of the community from the perspective of the Qur'an. This study uses a qualitative method by applying content analysis. This study discusses social media, the impact of social media on the social life of the people of the Al-Qur'an perspective, and the meaning of the impact of social media on the social life of the people of the Al-Qur'an perspective. This study concludes that the Qur'an explains the impact of things that are often found among the social media user community. The negative and positive impacts of social media require users to use social media wisely. The recommendation of this research is for other researchers to be able to examine this discussion further.